ANALISIS HUKUM TENTANG TINGKAT KESADARAN MASYARAKAT DALAM MELAPORKAN TINDAK PIDANA PENCURIAN KEPADA PIHAK KEPOLISIAN DI KOTA PEKANBARU - Safira, Dini Adelia; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In big cities like Pekanbaru City, many crimes occur because of a very dense population, a difficulteconomy, low education, and limited employment. As for crime, the intensity of which is currently increasingis theft. Whether it's theft in the house, or in crowded places such as in markets, on the streets, in publictransportation, and various other places. Indirectly, crime reports by the public can prevent the occurrenceof similar crimes from happening to others. By processing legally and providing a deterrent effect for theperpetrators to reduce other victims. The purpose of this thesis is; First, to find out the factors that influencethe community tend not to report criminal acts to the police, Second, to find out law enforcement efforts inincreasing public legal awareness.This type of research is sociological, because in this study the authors directly conducted research atthe location under study, in order to provide a complete picture of the problem under study. This researchwas conducted at the Pekanbaru City Police Department, while the population and sample were all partiesrelated to the problem studied in this study, the data sources used were primary data and secondary data,data collection techniques in this study with questionnaires, interviews, and studies literature.From the results of the study there were two main points that were concluded; First, the factors thatinfluence the community tend not to report criminal acts to the police in Pekanbaru City consist of nocertainty of stolen goods returned, a complicated process that requires no small cost, does not have legalknowledge, and does not have time to report. Second, law enforcement efforts in increasing public legalawareness are to increase cooperation between the police and the community, efforts to prevent crime andeducative efforts. The author's suggestion, First, To the Pekanbaru City Police Department can increasepublic legal awareness by conducting counseling, seminars, and other activities regarding the importance ofunderstanding the law and being in accordance with the law. Second, to the community to be able tocooperate and participate with the police in protecting the shared environment.Keywords : Legal Analysis ‒ Crime of Theft – Legal Awareness